Education of Women in Islam and Models of Kurdish Women Scientists - Hawri Omar Awla; Tareq Taher Abdulla (QALAAI ZANIST JOURNAL, 2021)
Islam cares about female, and provided them respect and patronage, inheritance, good upbringing and education. The right of education for female in Islam is not different from this right for male, through this study researcher tried to quickly clarify what the Islamic Sharia provide to female in terms of the rights to education and learning and Non-discrimination between them and males in this counter. The righteous women have a great role in the functioning of any society, they have a great role in the reformation and advancement of societies, as well as the spread of love and cooperation among people. While the invalid women have a great role in the deviation and backwardness of societies, and the spread of grudge and hatred among people. Women are half of the nation, then they give birth for the other half, they are an entire nation…. This study deals with the concept of educating female in Islam and examples of Kurdish women scientists. It showed the interest of Islam in educating female, and it included two Chapters. The first chapter: researcher mentioned the merit of knowledge, scholars, the right of education to female, and the ruling on their education. In the second chapter: researcher mentioned the care of the righteous ancestor in the education of female, and examples of Kurdish women scientists. The researchers reached several points and conclusions, which we mentioned in the conclusion.